Lo extramusical y su manifestación de lo real en el metal - Arboleda Alzate, Juan Camilo (Folios, revista de la Facultad de Comunicaciones y Filología, 2022)
From the cover of the album Dawn of the Black Hearts, of the norwegian group The True Mayhem, this article enters to the metal semantic field, which is how this network of texts that include express conditions that identify like a practice: this looks separated from the entertainment industry (where the hobby is volatilized and the profitable is first) and plans to focus on a selective appropriation that enables certain secrecy to its content. Without either are informational purposes, the message specializes and not become in a mass product. This definition of the message speaks of the configuration of the metal, his interest for exceeding moral restraints, to avoid surface readings and pleasure of representing an antagonistic style; satanism appears here like the demonic: not just like an Adversary from the christian order but from the ability to go further as a creative is not limited to what exists: the human being who, restless, widens the senses.